Dynamic Contrast-Enhanced MR Imaging Predicts Local Control in Oropharyngeal or Hypopharyngeal Squamous Cell Carcinoma Treated with Chemoradiotherapy - Ng, Shu-Hang (Public Library of Science, 2013)
The role of pretreatment dynamic contrast-enhanced perfusion MR imaging (DCE-PWI) and diffusion-weighted MR imaging (DWI) in predicting the treatment response of oropharyngeal or hypopharyngeal squamous cell carcinoma (OHSCC) to chemoradiation remains unclear. We prospectively investigated the ability of pharmacokinetic parameters derived from pretreatment DCE-PWI and DWI to predict the local control of OHSCC patients treated with chemoradiation. Between August, 2010 and March, 2012, patients with untreated OHSCC scheduled for chemoradiation were eligible for this prospective study. DCE-PWI and DWI were performed in addition to conventional MRI. The relationship of local control with the following clinical and imaging variables was analyzed: the hemoglobin level, T-stage, tumor location, gross tumor volume, maximum standardized uptake value, metabolic tumor volume and total lesion glycolysis on FDG PET/CT, transfer constant (K (trans)), volume of blood plasma and volume of extracellular extravascular space on DCE-PWI, and apparent diffusion coefficient on DWI of the primary tumor. The patients were also divided into a local control group and a local failure group, and their clinical and imaging parameters were compared. There were 58 patients (29 with oropharynx squamous cell carcinoma [SCC] and 29 with hypopharynx SCC) with successful pretreatment DCE-PWI and DWI available for analysis. After a median follow-up of 18.2 months, 17 (29.3%) participants had local failure, whereas the remaining 41 patients achieved local control. Univariate analysis revealed that only the K (trans) value was significantly associated with local control (P = 0.03). When the local control and local failure groups were compared, significant differences were observed in K (trans) and the tumor location (P = 0.01 and P = 0.04, respectively). In the multivariable analysis, only K (trans) was statistically significant (P = 0.04). Our results suggest that pretreatment K (trans) may help predict the local control in OHSCC patients treated with chemoradiation.